Virtual reality - Yount, Lisa; Gale Group (Detroit, Mich. Lucent Books, 2005)
Discusses the history of virtual reality, its uses, and the impact it has made on society.
Foreword -- Introduction -- Walking onto the holodeck -- Airplanes to arcades: the development of virtual reality -- Goggles, gloves, and caves: the technology of virtual reality -- The virtual classroom: virtual reality in training and education -- Custom-made worlds: virtual reality in science and business -- Arcades to avatars: virtual reality in art and entertainment -- Which world is real? the future of virtual reality -- Notes -- Glossary -- For further reading -- Works consulted -- Index -- Picture credits -- About the author.
Electronic reproduction.
Keywords: Virtual reality -- Juvenile literature; Electronic books